Beyond Plagiarism: ChatGPT and the Changing Meanings of Knowledge, Learning, and Academic Work in Pakistani Higher Education - Ali Raza; Eman Khalid; Ghulam Fatima (Policy Journal of Social Science Review, 2026)
Soon after the launch of ChatGPT and other generative artificial intelligence (GenAI) tools, the public in Pakistan got very interested in their use in university life. The attention was yet only narrowly given to plagiarism and cheating. Based on this paper, this is a very limited view. Based on a systematic review of recently done studies in Pakistani universities and supported by a wider international perspective on the uses of generative AI in higher education, the work presents a sociological understanding of how ChatGPT is redefying in three connected dimensions what is considered knowledge, how learning is carried out, and what academic work actually consists of. The work sets up a theoretical setup composed of the Social Construction of Technology (SCOT) and social constructionist theories of knowledge, which is then applied to interpret student and faculty perceptions, resource shortages, and response policies findings from Pakistani universities that were made public, placing them within a structure analysis of inequality. The paper concludes that higher education institutions in the Pakistani context are facing not just discipline issues, but a deeper sociological challenge: generative artificial intelligence is reworking who is allowed to speak on what they know, and with what proof, through whose work, in a system that was already stratified by class, language, and access. The paper ends with suggestions for future research and policy implications for the Higher Education Commission (HEC) as well as individual institutions. Keywords: ChatGPT; generative AI; academic integrity; Pakistani higher education; social construction of technology; social construction of knowledge. https://doi.org/10.5281/zenodo.21892033